JURNAL ILMU KEHUTANAN : Floristic Inventory of the Proposed Site for tarsier Tourism center in Villa Aurora, Bilar, Bohol, Philippines - Tomas D. Reyes Jr, Jeralyn B. Abadingo (Fakultas Kehutanan UGM, 2015)
The study assessed the present vegetation composition of the Proposed Site for the tarsierTourism Center (PTTC) at Villa Aurora, Bilar, Bohol and performed a comparative analysis with the existing Tarsier Sanctuary (TS) at Canapnapan, Corella, Bohol.